Elongation factor 1 alpha concentration is highly correlated with the lysine content of maize endosperm. - Habben, J E (1995)
Lysine is the most limiting essential amino acid in cereals, and for many years plant breeders have attempted to increase its concentration to improve the nutritional quality of these grains. The opaque2 mutation in maize doubles the lysine content in the endosperm, but the mechanism by which this occurs is unknown. We show that elongation factor 1 alpha (EF-1 alpha) is overexpressed in opaque2 endosperm compared with its normal counterpart and that there is a highly significant correlation between EF-1 alpha concentration and the total lysine content of the endosperm. This relationship is also true for two other cereals, sorghum and barley. It appears that genetic selection for genotypes with a high concentration of EF-1 alpha can significantly improve the nutritional quality of maize and other cereals.